Quasi‐2D Colloidal Semiconductor Nanoplatelets for Narrow Electroluminescence. (16th July 2013) - Chen, Zhuoying; Nadal, Brice; Mahler, Benoit; Aubin, Hervé; Dubertret, Benoit
<x xml:space="preserve">Abstract</x> The first functional light‐emitting diodes (LEDs) based on quasi 2D colloidal core/shell CdSe/CdZnS nanoplatelets (NPLs). The solution‐processed hybrid devices are optimized with respect to their electroluminescent characteristics, first, by improving charge injection through exchanging the as‐synthesized NPL long‐chain ligands to shorter ones such as 3‐mercaptopropionic acid, and second, by comparing different hole‐transporting layers. NPL‐LEDs exhibit a maximum luminance of 4499 cd m‐2 and external quantum efficiencies of 0.63%. In particular, over different applied voltages, systematically narrow electroluminescence of full width at half maximum (FWHM) in the range of 25–30 nm is observed to be independent from the choice of device configuration and NPL ligands. As spectrally narrow electroluminescence is highly attractive in terms of color purity in the context of LED applications, these results emphasize the unique potential of this new class of colloidal core/shell nanoplatelet in achieving bright and functional LEDs of superior color purity.